Search Title correct misconception in light of the book and Sunnah - Hussein , Nbras (Islamic Sciences Journal, 2023)
For serious understanding suqaim to Murad Alah's canon and for It is great harm on people , so the correction of conceptions has not been limited to our canon, instead we found it in other previous canons . - Correct misconceptions according to the light of the holy Quran and these conceptions are : ) holy men , guidness , gods , pessimism , death( - correct misconceptions according to the light of prophets sunnah , and these concepts are : ( the pond , the will , Doubt about the power of Alah on the resurrection , workship of pontiffs and monks).